Cultural studies, production et économie morale - Hesmondhalgh, David; Morin, Céline (Réseaux, 2015)
Les approches issues des cultural studies ont insufflé à la recherche sur les productions médiatiques et culturelles une vigueur nouvelle et nécessaire. Cependant, il devient de plus en plus clair au fil des ans qu’elles rencontrent également de sérieuses limites. L’évaluation menée dans cet article repose sur une première partie dans laquelle nous explorons, en profitant du recul historique, la période d’opposition entre les cultural studies et l’économie politique des années 1990, en distinguant ce que nous appelons les modes théorique et populiste des cultural studies. Nous esquissons ensuite les trois « écoles » des approches cultural studies vis-à-vis de la production et de l’économie : cultural economy, production studies, et creative industries analysis. Selon nous, ces approches en cultural studies de la production et de l’industrie dans le domaine de la culture pêchent, tant dans leur mode populiste que dans leur mode théorique, par le manque d’attention portée à des problématiques fondamentales liées à la normativité dans les rapports entre la culture, les médias et l’économie. Dans les deux dernières parties, portant sur le tournant du cultural labour et le concept d’économie morale, nous suggèrerons des solutions pour une prise en compte plus explicite des problèmes de normativité, proposant ainsi une base éthique potentiellement plus rigoureuse pour l’étude de questions importantes dans le champ de la production culturelle. Nous appliquerons succinctement ce système au rapport problématique entre les biens culturels et le bien-être dans les sociétés modernes., ENG: Cultural studies approaches have provided a welcome reinvigoration of research on media and cultural production. But, as the years go by, it becomes clearer that they also suffer from important limitations. To provide a basis for the assessment in this article, the first section revisits the 1990s moment of ‘political economy versus cultural studies’ with the benefit of hindsight, distinguishing what I call the theoretical and populist modes of cultural studies. I then outline three ‘schools’ of cultural studies approaches to production and economy : cultural economy, production studies, and creative industries analysis. My argument is that, in both its theoretical and populist modes, these cultural studies approaches to production and industry in the realm of culture suffer from a lack of attention to fundamental normative issues regarding the relationship between culture, media and economy. In the final two sections, which discuss the turn to cultural labour and the concept of moral economy, I offer suggestions for how key normative issues might be addressed in a more explicit way, potentially offering a more rigorous ethical grounding for important questions regarding the realm of cultural production. I briefly apply this to the problematic relationship between cultural goods and well-being in modern societies.
Communication; Media Studies
Keywords: cultural production; cultural studies; industry; moral economy

Communication Policy and the "Double Movement" - Ashley, Seth (Javnost-The Public, 2014)
Karl Polanyi's concept of a "double movement" has been used to describe the protectionist measures taken by governments to mitigate damage caused by the expansion of markets. Through a lens of political economy and historical institutionalism, this article uses Polanyi's framework to examine competing notions of the public interest as exemplified by the socially constructed nature of American and British broadcasting and the legitimating discourse that produced divergent outcomes. A historical analysis points to a decline of the double movement in communication policy, particularly in the U.S., and lends support to calls for noncommercial, public media structures and increased regulation of communication industries.
Communication Studies; Sociology
Keywords: communication policy; double movement; economic research; institutionalism (religion); marketing research; media system structure; protectionism

Neoliberalism as a state-centric class project: The Italian case - Briziarelli, Marco (Continuum: Journal of Media & Cultural Studies, 2011)
This essay sheds light on the neoliberal aspects of the Italian political-economic system exemplified in the relationship between capital, state and media. The main argument is that the specific marriage between neoliberalism and neocorporatism that characterizes Italy reveals a distinctive characteristic of neoliberalism: a class project relying heavily on the state. As Polanyi has suggested through the concept of 'embeddedness', capitalism has consistently developed through the double movement of preaching the independence of the free market from the state and requiring the state's protectionist interventions. After describing this state-centric framework to interpret neoliberalism, in the second part of the paper, I consider the political-economic history of Italy's recent decades, paying particular attention to the media system. I will examine the 'communicative performance' of neoliberalism in Berlusconi's discourses and concrete political decisions taken in the name of neoliberalism. The articulated relationship between media and politics reveals the continuous attempts by the advocates of neoliberalism to seize the state, not to reduce its intervention but in fact to manipulate the market.
Communication Studies; Media Studies; Cultural Studies
Keywords: Italy; economic indicators; essays; mass media audiences; neoliberalism; political economic analysis

Addressing the Negative Consequences of the Information Age Lessons from Karl Polanyi and the industrial revolution: A note on the politics of theorizing technology - Rogerson, Kenneth (Information, Communication & Society, 2003)
One of the great dilemmas of the information age is the tension between two dynamics: (1) the tendency of information to be free-flowing and not to lose its value as it moves and (2) the tendency to want to control that flow of information in order to profit from its value. In 1944, Karl Polanyi identified similar contradictions in the industrial revolution, except the flowing material was capital instead of information. He spent a lifetime exposing what he felt to be the negative consequences of this increasingly free-flowing capital, the hallmark of a free market economy. He advocated for a welfare state in which government intervention is necessary to control these negative effects. Given issues of the information age such as the digital divide, the commoditization of information, and security and privacy, as well as the arguments of the proponents and critics of these issues, Polanyi's concepts can provide insight into the complexities of increasingly technical and information-based societies.
Information Science; Media Studies
Keywords: industrial revolution; information technology

Chapter 7: Karl Polanyi - Rogerson, Kenneth S.; May, Christopher (Key Thinkers for the Information Society, 2002)
This article presents Karl Polanyi's analysis of the dynamic relationships between economy and society in the information age. Of the many concepts Karl Polanyi provides in his analysis of economic relations, three stand as carefully calculated assumptions about the relationship between society and economy: the embeddedness of information in society, the commoditization of information and the existence of a double movement in the information revolution. Information has always been embedded in societal interactions. To emphasize this point, he said that the simple flow of information seems to have little effect in and of itself on the outcome of social interchanges. In Polanyi's words, it is also embedded in other social relations, such as political, economic, cultural, or health-related discussions and actions. On the issue of information commoditization, Polanyi takes a different view. His logic indicates that there will be negative social consequences associated with it. One example is digital divide or the discrepancies on a global or national level between those who have access to information through new technologies and those who do not. With regards to the existence of double movement, Polanyi believed that there are two opposing forces-economic liberalism and social protection-present during the industrial revolution. However, this is not easy to see in the information age because of simple paradox. First, people who would eschew the uses of technology for ideological reasons,may turn to it for other reasons. And second, there is only a protest of a specific issue and not the imbalance of information flows or the ownership of information dissemination methods.
Information Science; Philosophy; Communications
Keywords: commercialization; communication revolution; digital divide; industrial revolution; information technology; liberalism